A ROCK1 Inhibitior Fasudil Alleviates Cardiomyocyte Apoptosis in Diabetic Cardiomyopathy by Inhibiting Mitochondrial Fission in a Type 2 Diabetes Mouse Model - Fan, Xinhui; Li, Xiaoxing; Liu, Huiruo; Xu, Feng; Ji, Xiaoping; Chen, Yuguo; Li, Chuanbao (Frontiers in Pharmacology, 2022)
Diabetes mellitus (DM) often involves cardiovascular complications; however, treatment regimens are limited. ROCK1 (rho-associated coiled-coil containing protein kinase 1) serves as a pathological factor in several diabetic complications. Herein, we aimed to explore the effect of Fasudil (a ROCK1 inhibitor) on the progress of cardiac dysfunction in type 2 DM (T2DM), and to explore the possible mechanisms. Type II diabetic mice models were established by inducing insulin resistance through a high-fat diet combined with low-dose streptozotocin (STZ) injection. NMCMs (neonatal mouse ventricular cardiac myocytes) in the control group were treated with 5.5 mM glucose, while those in the High Glucose (HG) group were treated with 33 mM glucose and 10 nmol/L insulin. In vivo, we found that type 2 diabetes enhanced the expression and activation of ROCK1 (p < 0.05). The ROCK1 inhibitor, Fasudil, prevented cardiac dysfunction, fibrosis, oxidative stress and myocardial ultrastructural disorders (p < 0.05) in the diabetic mice. In vitro, ROCK1 was upregulated in HG-induced cardiomyocytes, and ROCK1 inhibition using Fasudil reversed the increased apoptosis, consistent with in vivo results. Mechanistically, ROCK1 inhibition abrogated apoptosis, relieved mitochondrial fission, and efficiently attenuated the escalated production of reactive oxygen species in vitro and in vivo. The content of Ser616-phosphorylated dynamin-related protein 1 (Drp1) increased while ROCK1 led to apoptosis in HG-treated cardiomyocytes, which could be partly neutralized by ROCK1 inhibition with Fasudil, consistent with the in vivo results. Fasudil attenuated the cardiac dysfunction in diabetes by decreasing excessive mitochondrial fission via inhibiting Drp1 phosphorylation at serine 616.